Association between sleep duration and chest pain in US adults: A cross-sectional study - Chen, Wei; Wang, Ji-ping; Wang, Zi-min; Hu, Peng-Cheng; Chen, Yu (Frontiers in Public Health, 2022)
Objective: Herein, we purposed to explore the relationship of sleep duration with chest pain among adults in US. Methods: This research work enrolled 14967 subjects in the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2018. The relationship of sleep duration with chest pain Among Adults in US was evaluated by Multivariable logistic regression. Results: To elucidate the relationship, we made adjustments for gender, BMI, diabetes, smoking status, drinking status, race, marital status, annual family income, hyperlipoidemia, Hypertension. Chest pain incidence decreased by 4% [OR 0.96 (0.92, 0.99), p=0.018] for an increase in sleep duration by one hour. Smooth curve analysis showed a U-shaped relationship of sleep duration with incident chest pain. When duration of sleep was＜6.5 hours, chest pain incidence negatively correlated to sleep duration [OR 0.75 (0.69, 0.81) P<0.0001]. However, when sleep duration was ≥6.5 hours, chest pain incidence rose with escalating sleep duration [OR 1.10 (1.04, 1.16) p=0.001]. Conclusions: Duration of sleep was established to be independently linked with an increase in the occurrence of chest pain. Excessive sleep, as much as insufficient sleep, increases the risk of chest pain.